2010
DOI: 10.1007/s00425-010-1200-3
|View full text |Cite
|
Sign up to set email alerts
|

A proposed conserved role for an avocado fw2.2-like gene as a negative regulator of fruit cell division

Abstract: Previous studies using 'Hass' avocado and its small fruit (SF) phenotype as a model showed that SF is limited by cell number, not by cell size. In an attempt to explore the molecular mechanisms regulating avocado fruit cell division, we isolated four distinct avocado cell proliferation-related genes and investigated their expression characteristics, comparing normal fruit (NF) and SF developmental patterns. Three cDNAs termed PaCYCA1, PaCYCB1 and PaPCNA, encoding two mitotic cyclins and a proliferating cell nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 60 publications
2
39
0
3
Order By: Relevance
“…The differences in unigene number and length between our results and Luo et al (2014) are probably due to the different sequencing strategies, that is, the sample preparation, sequencing platforms and assembly programs. It was reported that the expression level of Pafw2.2-like was higher in smaller fruits than in normal fruits of 'Hass' in avocado (Cowan et al, 1997;Dehan et al, 2010;Zilkah and Klein, 1987). FW2.2/CNR family genes are known to be associated with the regulation of fruit cell number in tomato (Frary et al, 2000) and sweet cherry (De Franceschi et al, 2013).…”
Section: Transcriptome Analysis Of Htn and Ttn Fruitsmentioning
confidence: 99%
See 2 more Smart Citations
“…The differences in unigene number and length between our results and Luo et al (2014) are probably due to the different sequencing strategies, that is, the sample preparation, sequencing platforms and assembly programs. It was reported that the expression level of Pafw2.2-like was higher in smaller fruits than in normal fruits of 'Hass' in avocado (Cowan et al, 1997;Dehan et al, 2010;Zilkah and Klein, 1987). FW2.2/CNR family genes are known to be associated with the regulation of fruit cell number in tomato (Frary et al, 2000) and sweet cherry (De Franceschi et al, 2013).…”
Section: Transcriptome Analysis Of Htn and Ttn Fruitsmentioning
confidence: 99%
“…The FW2.2/CNR family of genes controls organ size by modulating cell numbers in other plant species such as avocado (Persea americana Mill. ; Dehan et al, 2010) and sweet cherry (De Franceschi et al, 2013). In avocado, the expression level of Pafw2.2-like was higher in the smaller fruits of 'Hass' trees than in normal fruits (Cowan et al, 1997;Dehan et al, 2010;Zilkah and Klein, 1987).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following successful germination, plant growth depends on a combination of two essential processes; cell division and cell expansion. These two processes play essential roles in the determination of plant size [13]. The growth-limiting effects of various kinds of stress have been related to their effects on the regulation of elongation and cell division [10].…”
Section: Osdpr Suppresses Growth Of Transgenic Tobacco Plantsmentioning
confidence: 99%
“…Interestingly, silencing of GmFWL1 expression resulted in greater condensation of cellular chromatin. Other, more distantly related FWL gene family members include PaFWL, 10 shown to regulate avocado fruit development. Other family members have been implicated as regulators of calcium influx (AtMCA1 11,12 ), as of the number and location of cysteine residues, FWL and PLAC8 core domains share similar tertiary structures and potentially similar biochemical functions.…”
Section: Notementioning
confidence: 99%